PENGARUH WORK-LIFE BALANCE TERHADAP WORK ENGAGEMENT PADA DOSEN WANITA DALAM MENGHADAPI DUNIA PENDIDIKAN DI ERA DIGITAL - Rahmayati, T. Elfira; Sariyanto, Sariyanto; Adriansyah, T.M (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to determine how much influence work-life balance has on work engagement for women in dealing with the world of education in the digital era. Technological developments in the digital era in today's world of education encourage them to develop their ability to operate digital systems both in communicating, teaching and learning and using applications to support the tri dharma task of higher education. The demands of work duties and responsibilities are a challenge for lecturers to do many things in daily life in a balanced way. Especially as a female lecturer who is also responsible for taking care of household activities. In addition, lecturers as human resources in universities are also a source of lessons to be responsible for the development and quality of universities as their organizations. This requires lecturers to be heavily involved in the administration and activities set by the institution. The involvement of lecturers makes the higher education system run smoothly and creates a satisfactory quality of higher education. With a balance between work and life, it is hoped that female lecturers can be more involved in all matters so that the tasks and responsibilities of the organization can be achieved. Measurements were carried out on 200 respondents using the Urtretch Work Engagement Scale and the work life balance scale. The results show that there is a positive and significant effect of work life balance on work engagement on female lecturers, which is 87.1%